Monitoramento hidrossedimentométrico e avaliação da produção de sedimentos em eventos chuvosos em uma pequena bacia hidrográfica urbana de encosta - Bellinaso, Tarcisio Barcellos (2002)
With the development of the civilizations and the consequent populational growth on the entire world, grown too, on accelerated form, the use of available hydric resources. The construction of hydraulic works and the devastation of the ciliary forest, between other anthropic actions, change the natural conditions where they occur, bringing with them problems like inundations of areas and your effects upon the fauna and flora, erosion, transport and deposition of sediments , etc. The present work have as objective to evaluate, from measurements of solid discharge, the production of sediments in a little hydrographic basin of slope, on process of urbanization, with 0,53 km2 of area, on rainy events and compare it with results obtained by the Modified Universal Soil Loss Equation (MUSLE), Williams (1975). Was made hydro-sedimentmetric monitoring and determined the physical features of the hydrographical basin. Were evaluated 10 events measured on the period from April 19th of 2001 to December 3rd of 2001. The MUSLE, as method of prevision to sediments quantities, show itself inadequate on the hydrographical basin studied, superstimating the measured valor, nevertheless using data of drainage volume and peak of flow obtained from field measurements. Was made the adjust of the parameters of MUSLE, obtaining results similar to that observed by Branco (1998), to a rural basin located on the same region. The data observed allowed a good adjust of the sediment-rating curve and showed a concordance with results of MUSLE with adjusted parameters.